A new mesogenic mixture with antiferroelectric phase only at a broad temperature range. Issue 10 (8th August 2016) - Żurowska, Magdalena; Morawiak, Przemysław; Piecek, Wiktor; Czerwiński, Michał; Spadło, Anna; Bennis, Noureddine
ABSTRACT: New compounds (S)-4ʹ-(1-methylheptyloxycarbonyl)biphenyl-4-yl 4-[3-(2, 2, 3, 3, 4, 4, 5, 5, 5-nonafluoropentyloxy)prop-1-oxy]benzoates were synthesised and characterised. Their mesomorphic properties were tested by means of polarising optical microscopy and differential scanning calorimetry. The multicomponent antiferroelectric high tilt mixture with long pitch has been also formulated and characterised. The helical pitch of prepared mixture was estimated with selective reflection method. GRAPHICAL ABSTRACT: